Toleransi Beragama Masyarakat Bali, Papua, Maluku - Ainna Amalia; Ricardo Freedom Nanuru (IAI Darussalam, 2018)
The focus of this research is the tolerance of the people of Bali, Maluku, and Papua. This quantitative research uses a survey method by taking 282 respondents who are at least 20 years old. As a result, 61.3% of respondents were the same with people of different religions and religions. 85.3% remained friends despite their religious differences. 60.6% of respondents still feel happy and comfortable with people who have different beliefs. And 66.3% of respondents often gave appreciation to friends and neighbors of different religions. Respondents also strongly disagree if there are actions that prevent adherents of other religions from carrying out their worship, which is as much as 78.5%. They tend to give freedom of worship to different followers, as many as 84.9%. In addition, as many as 56.3% of respondents released adherents of other religions to establish places of worship as long as they were in accordance with procedures. And 61.3% of respondents continued to establish cooperation in various fields with people of different religions. Conclusions from research conducted, the people of Bali, Maluku, and Papua, which are Muslim minority areas, still have a high tolerance towards other religions. So religious differences do not affect their tolerance